2020
DOI: 10.1089/cap.2019.0087
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Monitoring Rates of Youth Treated with Second-Generation Antipsychotics in Usual Care: Results of a Large US National Commercial Health Plan

Abstract: Objectives: To examine metabolic monitoring rates in commercially insured children and adolescents treated with a secondgeneration antipsychotic (SGA) during calendar years (CYs) 2016 and 2017. Methods: In this retrospective study, data were collected from a large national commercial health plan for the period covering January 1, 2016 to December 31, 2017. Commercially insured children and adolescents, aged 8-19 years with ‡2 SGA prescription claims during the CY, were identified for the CY2016 and CY2017 coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…Although previous studies have shown differences in monitoring frequencies in children treated with antipsychotic drugs, it is clear that the monitoring frequencies were suboptimal (13,15,16,18). Overall, it has been shown that the physical parameter weight was monitored more frequently in children treated with antipsychotic drugs compared to the laboratory parameters glucose and lipids, and waist circumference was monitored much less, which is in line with the results of this current study (14,15,19).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although previous studies have shown differences in monitoring frequencies in children treated with antipsychotic drugs, it is clear that the monitoring frequencies were suboptimal (13,15,16,18). Overall, it has been shown that the physical parameter weight was monitored more frequently in children treated with antipsychotic drugs compared to the laboratory parameters glucose and lipids, and waist circumference was monitored much less, which is in line with the results of this current study (14,15,19).…”
Section: Discussionsupporting
confidence: 89%
“…Monitoring instructions of these parameters are available in clinical guidelines, and in regulatory drug product information such as the information leaflet (9)(10)(11)(12). Despite the existing guidelines and instructions, previous studies have shown a large variability in the monitoring frequencies of ADR-related parameters, and that the overall monitoring frequencies were suboptimal (13)(14)(15)(16). The majority of these studies used administrative databases from various settings, such as insurance companies or databases of general practitioners, but questionnaires about monitoring among prescribers have also been assessed (14,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aripiprazole (32.2%), risperidone (30.4%), and quetiapine (14.9%) were the most commonly preferred antipsychotic drugs of the physicians involved in our study. Recent studies have indicated that risperidone, aripiprazole, and quetiapine are the three most commonly prescribed antipsychotics (Huskamp et al 2016;Hálfdánarson et al 2017;Hayden et al 2020). In a study conducted in our country, the order of antipsychotic preference in children and adolescents admitted to outpatient clinics was found as risperidone, aripiprazole, and quetiapine (Yektas x and Tufan 2018).…”
Section: Discussionmentioning
confidence: 90%
“…Fifteen papers were identified for inclusion in this review comprising four studies of self-reported clinical practice (Curtis et al, 2012;McLaren et al, 2017;Rodday et al, 2015;Walter et al, 2008) (Table 1), five data linkage studies of metabolic monitoring in children and adolescents attending mental health services (Connolly et al, 2015;Hayden et al, 2019;Morrato et al, 2010;Okumura et al, 2018;Raebel et al, 2014) (Table 2) and six retrospective chart review studies to examine metabolic monitoring (Cotes et al, 2017;Coughlin et al, 2018;Featherston et al, 2018;Javaheri and McLennan, 2019;Kauffman et al, 2018;Wakefield et al, 2019) (Table 3). Of the 11 studies which reported data from child and adolescent patients, five provided information about the diagnoses of the children (Connolly et al, 2015;Coughlin et al, 2018;Featherston et al, 2018;Hayden et al, 2019;Morrato et al, 2010). The diagnoses provided were wide ranging and representative of children attending a specialist mental health service.…”
Section: Resultsmentioning
confidence: 99%